Effect of Photo-Selective Shade Nets on Pollination Process and Nut Development of Corylus avellana L. - Guastella, Devid; Sigwebela, Mbuyseli; Suarez, Eloy; Stubbs, Oscar; Acevedo, Jorge; Engelbrecht, Gerhard (Frontiers in Plant Science, 2020)
Hazelnut (Corylus avellana L.) is one of the most appreciated nut crops, which is motivating the cultivation outside its historical production areas. Despite that, there is still limited knowledge about the floral biology of the species and its developmental fruiting stages under different environments. Adverse climatic conditions can threaten the pollination process and fruit development. In South Africa, the deciduous fruit industry identified the net shading as a tool to mitigate the effects of unfavorable abiotic events. The objective of this work was to investigate the effects of photo-selective nets on the pollination process and nut development of C. avellana. Mature hazelnut trees were maintained under netting and compared with the ones in open field. Microscopic examination of female flower and developing nuts were conducted in order to observe the pollen tube growth and the pattern of disodium fluorescein transport into the funiculus and ovule. The results showed clear differences in pollen tubes growth and timing between the tests. Generally, trees under nets showed higher rate in pollen tubes developing and reaching the base of the style. On the contrary, the tests carried out in open field showed a higher ratio of pollen tubes arrested in the style. The results also indicated differences in ovules abortion. Developing fruits that showed an interruption point at the funicle level or at junction point of the ovule, were classified as aborting fruits (blank nuts at harvest time). A higher rate of abortion was detected in open field compared to the plants under netting. In conclusion, the shade nets inﬂuenced the pollen tube growth and the nut development, principally due to micro-climate modiﬁcation.